Copper‐Catalyzed Electrophilic Etherification of Arylboronic Esters with Isoxazolidines. Issue 12 (25th May 2020) - Katahara, Seiya; Takahashi, Tenga; Nomura, Kengo; Uchiyama, Masanobu; Sato, Takaaki; Chida, Noritaka
Abstract: A copper‐catalyzed electrophilic etherification of arylboronic esters is reported. Isoxazolidines are utilized as easily available and stable [RO] + surrogates to give 1, 3‐amino aryl ethers. The O ‐selective arylation of isoxazolidines takes place without causing competitive N ‐arylation. In contrast to previously reported anionic conditions, our copper‐catalyzed conditions are mild enough to achieve high functional group tolerance. Preliminary mechanistic studies and DFT calculations support that the reaction proceeds via a transmetalation/oxidative addition pathway, followed by a Lewis acid‐promoted reductive elimination to induce the crucial O ‐selectivity. Abstract : A copper‐catalyzed electrophilic etherification of arylboronic esters with isoxazolidines has been reported. The salient features of our method are 1) highly functionalized and stable isoxazolidines as electrophilic oxygen sources, 2) unprecedented O ‐selective arylation of isoxazolidines associated with N−O bond cleavage, and 3) high functional group tolerance compared with anionic conditions.